Breast cancer radiotherapy and risk of pacemaker implantation: an epidemiologic analysis using the French nationwide claims database. (14th October 2021) - Errahmani, M Y; Thariat, J; Ferrieres, J; Bernier, M O; Boveda, S; Jacob, S
Abstract: Background: Radiotherapy (RT) is a major treatment for breast cancer (BC), but it is also associated with an increased long-term (>5–10 years) risk of cardiac complications. Specific data on cardiac arrhythmias and conduction disorders are warranted. Purpose: To evaluate whether pacemaker (PM) implantation risk is higher in BC patients treated with RT compared to the general population or population of BC patients treated without RT. Methods: Our study was based on the Echantillon Généraliste de Bénéficiaires (EGB), the 1/97 random sample of the French nationwide health insurance claims database. The population of patients treated for BC consisted of adult women with a first BC identified by the ICD-10 diagnosis codes between 2008 and 2016, and followed through 2018. PM implantations and RT were identified with medical procedures codes in the french Common Classification of Medical Procedures (CCAM). For each year from 2008 to 2018, the reference population included all adult women of the EGB database. History of PM or BC was an exclusion criteria. Annual incidence rates of PM implantations were evaluated between 2008 and 2018 in the reference populations. The number of PM cases observed in BC patients at least one year after BC diagnosis was compared with the expected number of PM cases calculated by using reference incidence rates with age standardization. We then computed the standardized incidence ratio (SIR) as the ratio of the observed number of PM to the expected number of PM, with 95% confidence intervals (CIs). Thereafter, a survival analysis was performed in BC patients using a Cox regression model (Hazard Ratio – HR) in order to evaluate the risk of PM associated with treatment including RT (RT) compared with treatment not including RT (no RT). Results: A total of 3, 853 patients were included in the population of patients treated for BC between 2008 and 2016 with a mean age of 60 years old and a mean follow-up of 5.6 years. In this population, 35 cases of PM were observed, compared with 19.9 expected cases of PM, corresponding to a significant SIR=1.76 (95% CI: 1.22 - 2.39). This excess risk was carried by the RT group of 2973 patients (77% of BC population): 28 observed PM vs 12.9 expected, SIR=2.18 (95% CI: 1.45–3.06). In Cox regression analysis, after adjustment on age, RT was associated with an increased risk of PM compared with no RT, but this result did not reach statistical significance (HR=1.73; p-value=0.21). Conclusion: Based on our study, BC patients receiving RT appeared to be at higher risk of PM implantation than general female population and BC patients without RT, illustrating a potential association between cardiac exposure during BC RT and conduction disorders. FUNDunding Acknowledgement: Type of funding sources: None.